A cross-sectional study on the knowledge and use of psychoactive substances among pregnant women attending the antenatal clinic at Oke-Eletu Primary Health Centre, Ijede, Ikorodu, Lagos State. - Tabitha Amere, Leslie; Tata, Danlami Leslie; Adeleye Udo, Victoria; Kiazolu-Sudieh, Satta; Oluwatoyin Mutiat, Okusanya (Student's Journal of Health Research Africa, 2025)
Introduction This study assessed the knowledge and use of psychoactive substances among pregnant women attending the antenatal clinic at Oke-Eletu Primary Health Centre, Ijede, Ikorodu, Lagos State, Nigeria. Methodology A cross-sectional descriptive study design was adopted for the study, and the target population was pregnant women attending the antenatal clinic at Oke-Eletu Primary Health Centre, Ijede, Ikorodu, Lagos State. A purposive non-probability sampling method was used to select a total of 174 respondents. Data was collected using the researchers' self-structured questionnaire and analyzed using SPSS Version 25, and presented in descriptive and inferential statistics, respectively. Results Findings revealed that about 29.3% had poor knowledge of psychoactive substances. Agbo (Alcohol/water-based herbal concoction) (37.9%) and (25.9%) have been used before and are currently in use. About two-thirds (63.8%) agreed that psychoactive substance has no beneficial effect, and the majority (79.3%) of the respondents agreed that psychoactive substance hurts pregnant women, with effects such as the development of chronic disease (50.0%), false perception (25.4%), addiction (9.4%), and poor judgment (8.0%). For the frequency of psychoactive substance use among the respondents, about 41.4% never used psychoactive, 25.9% use it often, 22.4% rarely used it, while 10.3% used it very often and the respondents reason for using psychoactive substance, more half (53.4%) agreed that psychoactive substance use to relieve pain, 37.9% for cultural reason, because it helps them to eat better (36.2%) because of peer pressure (32.8%) and it reduces stress (31.0%). Lastly, there is a significant relationship between knowledge of psychoactive substances and the use of psychoactive substances (p-value <0.001) Conclusion A few of the respondents had poor knowledge of psychoactive substances. Recommendation There is a need for continuous health educational intervention to boost the respondents’ knowledge about the health consequences of the use of psychoactive substances.